Composing Pedagogical Identities: Digital Music-Making, Islamic Values, and Local Culture in Early Childhood Teacher Education - Bahtiar Arbi; Adi Suprayogi; Brian Trinanda Kusuma Adi; Risali Salama (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2026)
Objective: Digital transformation in arts education has opened new avenues for prospective teachers to explore creativity through technology. This study aims to examine the experiences of students from the Early Childhood Islamic Education (PIAUD) Program in composing children’s songs that integrate Islamic values and local cultural elements using the digital music platform BandLab. Method: Employing an arts-based research approach combined with narrative inquiry, the study involved six students who produced original children’s songs as part of their final project in a music composition course. Data were collected through documentation of musical works (audio and visual), reflective writing, and narrative interviews. Result and Discussion: The findings reveal that students successfully embedded Islamic messagessuch as worship, ethics, and prophetic stories into simple yet educational musical structures suitable for early childhood. Local cultural elements, including regional vocabulary, rebana-inspired rhythmic motifs, and pentatonic melodic patterns, also emerged within their compositions. Narrative reflections highlight that the digital music-making process encouraged students to grow as creative, spiritually grounded, and technologically literate educators. This study underscores the potential of digital platforms like BandLab as pedagogical tools in Islamic early childhood music education and advocates for a more responsive curriculum aligned with the realities of the digital era. Conclusion: This study contributes to the growing body of knowledge on digital arts education by demonstrating how the integration of Arts-Based Research, digital music technology, Islamic values, and local culture can serve as an innovative pedagogical model in early childhood teacher education. It also offers practical implications for designing teacher education curricula that foster creativity, cultural responsiveness, and digital literacy in the era of educational transformation.